Pesona Nikel Indonesia Kurang Memikat Tesla - Fandy Kusuma Faizal; Muchran Fajrin; Ilyas Sibali (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to determine the development of Tesla's investment in Indonesia related to one of the Natural Resources, which is now the favorite of investors, Nickel. This empirical research method uses normative research. The study results show that many people need to learn the cause of the failure of Tesla's investment in Indonesia due to the issue of implementing ESG (Environmental, Social, and Governance). ESG values are company practice values that refer to three things: the environment, social impact, and good regulatory governance. As long as Nickel mining in Indonesia is carried out in ways that are not environmentally friendly and damage nature, don't expect Tesla (Elon Musk) to invest in Indonesia.